INTELLIGENCE AS A PSYCHOLOGICAL AND PEDAGOGICAL PROBLEM: THE ESSENCE OF THE CONCEPT AND SUBSTANTIVE CHARACTERISTICS (Pedagogy of Higher and Secondary Education, 2022)
The problem of intellect at the psychology-pedagogical aspect is illuminate at the article, the essence of idea and it's contain characteristics have been discovered.
Keywords: intellect the model of intellect; general intellectual abilities; intellectual characteristics; intellectual development